2021
DOI: 10.1186/s40550-021-00083-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of toxic metals and assessment of health risk in agricultural products food from Markazi Province of Iran

Abstract: The current study aims to investigate the levels of the toxic metal in agricultural products (legumes, wheat, and potato) collected in Markazi province, Iran, and human health risk by using inductively coupled plasma - optical emission spectrometry (ICP-OES). The levels of arsenic (As) and cadmium (Cd) in all samples were lower than the limit of detection (LOD), while the level of Cd in potato samples was lower than the maximum permisible level (MPL) of the European commission (EC). The non-carcinogenic and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…According to the EPA procedure, Monte Carlo Simulation was performed in the probabilistic hazard evaluations to reduce the uncertainties of the hazard predictions with probability assignment for each variable to elude underestimation or overestimation ( 30 , 32 , 33 , 39 ). For this purpose, several research studies have been done on the assessment of probabilistic health risk by using Monte Carlo Simulation for PAH S in infant formulae in Iran ( 18 ), arsenic in infants Dietary intake in the USA ( 40 ), PAHs in mushrooms (raw, grilled, and fried) ( 8 ), trace elements and sulfur dioxide residual in raisins ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the EPA procedure, Monte Carlo Simulation was performed in the probabilistic hazard evaluations to reduce the uncertainties of the hazard predictions with probability assignment for each variable to elude underestimation or overestimation ( 30 , 32 , 33 , 39 ). For this purpose, several research studies have been done on the assessment of probabilistic health risk by using Monte Carlo Simulation for PAH S in infant formulae in Iran ( 18 ), arsenic in infants Dietary intake in the USA ( 40 ), PAHs in mushrooms (raw, grilled, and fried) ( 8 ), trace elements and sulfur dioxide residual in raisins ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have shown that long-term exposure to microplastics is highly associated with cancer development in humans and animals (Karimi et al 2021 ). Due to their small size, microplastics can be directly consumed by various marine organisms and contaminate the human food chain via the bioaccumulation process (Zhao 2022 ).…”
Section: Detrimental Effects Of Microplastics Ingestion On Human Healthmentioning
confidence: 99%
“…In addition, heavy metals such as arsenic (As), cadmium (Cd), chromium (Cr), mercury (Hg), and lead (Pb) used in the production of plastics are carcinogenic, according to the International Agency for Research on Cancer (IARC). Epidemiological studies have shown that long-term exposure to microplastics is highly associated with cancer development in humans and animals (Karimi et al 2021). Due to their small size, microplastics can be directly consumed by various marine organisms and contaminate the human food chain via the bioaccumulation process (Zhao 2022).…”
Section: Microplastic-induced Cancermentioning
confidence: 99%
“…Another study in this province showed that the carcinogenic and noncarcinogenic index of mercury in milk is unsafe for children (Karimi, Rezaei, et al, 2021). The Angoran lead and zinc mine, situated in Mahenshan city, Zanjan province, Iran (36 • 37′ N and 47 • 24′ E), stands as a prominent entity within the Middle East's mining landscape.…”
Section: Highlightsmentioning
confidence: 99%